A Note on High Yield Pulping of Wheat Straw - Bhandari, K. S.; Srivastava, Anita; Sharma, Y. K. (Indian Forester, 1984)
High yield pulping of wheat straw was carried out using sodium hydroxide and a mixture of sodium hydroxide + Sodium carbonate as pulping chemicals. Anthraquinone was used as a pulping additive. On the basis of series of experiments, it was observed that pulps with almost similar pbysical strength properties could be obtained by using 2% NaOH + 6% Na2CO2, 4% NaOH + 2% Na2CO3 and 6% NaOH. However, pulp yield was slightly higher in case of 2% NaOH + 6% Na2CO3. From the present study it was concluded that sodium hydroxide could be replaced partially by sodium carbonate without adversely affecting the quality and quantity of pulp produced.